2015
DOI: 10.2196/mhealth.4930
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Apps for Schizophrenia: A Systematic Review

Abstract: BackgroundThere is increasing interest in using mobile technologies such as smartphones for improving the care of patients with schizophrenia. However, less is known about the current clinical evidence for the feasibility and effectiveness of smartphone apps in this population.ObjectiveTo review the published literature of smartphone apps applied for the care of patients with schizophrenia and other psychotic disorders.MethodsAn electronic database search of Ovid MEDLINE, the Cochrane Central Register of Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
194
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(210 citation statements)
references
References 30 publications
11
194
1
4
Order By: Relevance
“…A recent meta-analysis on smartphone ownership in psychotic patients revealed that it was increasing rapidly, with 81.4% ownership among respondents between 2014 and 2015 in the United States [23]. Another study carried out in Georgia in year 2015, with a sample of 80 patients with schizophrenia, concluded that there was greater access to smartphones in front of computers in the studied sample (73% vs. 54%), which would also be compatible with our results [20].…”
Section: Comparison With Prior Worksupporting
confidence: 90%
“…A recent meta-analysis on smartphone ownership in psychotic patients revealed that it was increasing rapidly, with 81.4% ownership among respondents between 2014 and 2015 in the United States [23]. Another study carried out in Georgia in year 2015, with a sample of 80 patients with schizophrenia, concluded that there was greater access to smartphones in front of computers in the studied sample (73% vs. 54%), which would also be compatible with our results [20].…”
Section: Comparison With Prior Worksupporting
confidence: 90%
“…The smartphone, which enables digital engagement with patients in real time and real environments [48], may facilitate this process through easy and timely access to support. Firth and Torous [49] have documented high rates of engagement and satisfaction with apps in the care of people with schizophrenia. This further encourages the nascent potential of the mode of service delivery to accommodate the needs of young adults with schizophrenia at all times.…”
Section: Discussionmentioning
confidence: 99%
“…Apps for a variety of mental health disorders/medical conditions such as depression,18 schizophrenia,19 bipolar affective disorder,20 cancer21 and diabetes22 have been previously reviewed. However, no review of social anxiety apps has been undertaken previously.…”
Section: Introductionmentioning
confidence: 99%